What does it mean to flourish, languish, and grow? A qualitative analysis of civilian interviews from survivors of the 1994 Rwandan genocide - Linn Zapffe; Kaitlyn Hennig; Nuwan Jayawickreme; Eranda Jayawickreme (Elsevier, 2023)
The current study investigated characteristics of resilience and posttraumatic growth in a sample of Rwandan genocide survivors. One hundred and sixty-three participants provided responses to a series of open-ended questions about resilient functioning among members of their community, as well as their own experiences of posttraumatic growth since the genocide. An overall theme in the responses was the role of environmental characteristics in both resilience and posttraumatic growth, which was apparent through the high frequency of codes such as family, means, work, and education. Furthermore, there was considerable overlap in identified domains of resilient functioning and posttraumatic growth. The results suggest that in this particular context, resilience is predominantly characterized by environmental features rather than individual characteristics. This has implications for interventions in Rwanda as well as the validity of current models and measures of resilience and posttraumatic growth in different cultures.